2017
DOI: 10.1177/0284185117710051
|View full text |Cite
|
Sign up to set email alerts
|

Early evaluation of radiation-induced parotid damage with diffusion kurtosis imaging: a preliminary study

Abstract: Background Radiation-induced parotid gland damage is a common complication of radiotherapy (RT) in patients with nasopharyngeal carcinoma (NPC), which always causes xerostomia, dysphagia, dental caries, and even sleep disorders. Early evaluation of radiation-induced parotid damage is required to facilitate early interventions. Purpose To early-evaluate radiation-induced parotid damage using diffusion kurtosis imaging (DKI) in patients with NPC undergoing RT. Material and Methods Thirty-two patients with NPC un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…The study found that MD of bilateral PG, SMG, and SLG at mid-RT (t3) and post-RT (t4) significantly increased while MK decreased compared with that of pre-RT, and the comparison between mid- and post-RT was also significant. The trend of MD is in accord with the change in ADC that had been reported in a previous study ( 10 ), which also corroborates the research on evaluation of RT-induced salivary gland damage ( 21 , 24 , 25 ). The increase in MD suggested increased water diffusivity as a result of RT-induced apoptosis of acinar cells and decrease in tissue cellular packing density ( 6 , 10 , 22 ) while reduced MK depends on the structural complexity of the glands ( 20 , 21 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The study found that MD of bilateral PG, SMG, and SLG at mid-RT (t3) and post-RT (t4) significantly increased while MK decreased compared with that of pre-RT, and the comparison between mid- and post-RT was also significant. The trend of MD is in accord with the change in ADC that had been reported in a previous study ( 10 ), which also corroborates the research on evaluation of RT-induced salivary gland damage ( 21 , 24 , 25 ). The increase in MD suggested increased water diffusivity as a result of RT-induced apoptosis of acinar cells and decrease in tissue cellular packing density ( 6 , 10 , 22 ) while reduced MK depends on the structural complexity of the glands ( 20 , 21 ).…”
Section: Discussionsupporting
confidence: 91%
“…The trend of MD is in accord with the change in ADC that had been reported in a previous study ( 10 ), which also corroborates the research on evaluation of RT-induced salivary gland damage ( 21 , 24 , 25 ). The increase in MD suggested increased water diffusivity as a result of RT-induced apoptosis of acinar cells and decrease in tissue cellular packing density ( 6 , 10 , 22 ) while reduced MK depends on the structural complexity of the glands ( 20 , 21 ). Decreased diffusion kurtosis together with increased mean diffusivity may indicate increased extracellular space within the voxel of interest.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The performance of the models may be underestimated by the fact that they were evaluated on the internal test set after a stratified 5-fold cross-validation, which may not be representative of the entire data set due to the small sample size. We did not include ADC/D t histogram analysis, though it was suggested by others [ 45 ] that early changes in the highest ADC percentiles correlated to Grade 2 xerostomia and could be clinically useful. Future investigations will include the role of D t histogram analysis in particular, with the aim of improving the sensitivity of the classification model.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity to the salivary glands is dose‐dependent, and although toxicity related to lower doses (20–30 Gy) is reversible, higher doses (>50 Gy) carry the potential for irreversible damage 9 . The most susceptible to prolonged damage are the parotid glands 10,11 . Symptoms can be debilitating and may significantly affect quality of life, including chronic pain, constant or recurrent swelling of one or more glands, and xerostomia that causes odynophagia and dysphagia.…”
Section: Introductionmentioning
confidence: 99%